(untitled) (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
ANNOTATION In the process of a small research, the translator's skills in the field of literary translation, the features of translating words and phrases are studied. At the same time, the poems describe the subtleties of the translation of some words and recommendations in this regard.